Changes in demographics, clinical practices and long-term outcomes of patients with ST segment-elevation myocardial infarction who underwent coronary revascularisation in the past two decades: cohort study. Issue 3 (31st March 2021) - Takeji, Yasuaki; Shiomi, Hiroki; Morimoto, Takeshi; Yoshikawa, Yusuke; Taniguchi, Ryoji; Mutsumura-Nakano, Yukiko; Yamamoto, Ko; Yamaji, Kyohei; Tazaki, Junichi; Kato, Eri Toda; Watanabe, Hirotoshi; Yamamoto, Erika; et al.
Abstract : Objective: To evaluate changes in demographics, clinical practices and long-term clinical outcomes of patients with ST segment-elevation myocardial infarction (STEMI) before and beyond 2010. Design: Multicentre retrospective cohort study. Setting: The Coronary Revascularization Demonstrating Outcome Study in Kyoto (CREDO-Kyoto) AMI Registries Wave-1 (2005–2007, 26 centres) and Wave-2 (2011–2013, 22 centres). Participants: 9001 patients with STEMI who underwent coronary revascularisation (Wave-1: 4278 patients, Wave-2: 4723 patients). Primary and secondary outcome measures: The primary outcome was all-cause death at 3 years. The secondary outcomes were cardiovascular death, cardiac death, sudden cardiac death, non-cardiovascular death, non-cardiac death, myocardial infarction, definite stent thrombosis, stroke, hospitalisation for heart failure, major bleeding, target vessel revascularisation, ischaemia-driven target vessel revascularisation, any coronary revascularisation and any ischaemia-driven coronary revascularisation. Results: Patients in Wave-2 were older, more often had comorbidities and more often presented with cardiogenic shock than those in Wave-1. Patients in Wave-2 had shorter onset-to-balloon time and door-to-balloon time, were more frequently implanted drug-eluting stents, and received guideline-directed medication than those in Wave-1. The cumulative 3-year incidence of all-cause death was not significantly different between Wave-1 and Wave-2 (15.5% and 15.7%, p=0.77). The adjusted risk of all-cause death in Wave-2 relative to Wave-1 was not significant at 3 years (HR 0.92, 95% CI 0.83 to 1.03, p=0.14), but lower beyond 30 days (HR 0.86, 95% CI 0.75 to 0.98, p=0.03). The adjusted risks of Wave-2 relative to Wave-1 were significantly lower for definite stent thrombosis (HR 0.59, 95% CI 0.43 to 0.81, p=0.001) and for any coronary revascularisation (HR 0.75, 95% CI 0.69 to 0.81, p<0.001), but higher for major bleeding (HR 1.34, 95% CI 1.20 to 1.51, p=0.005). Conclusions: We could not demonstrate improvement in 3-year mortality risk from Wave-1 to Wave-2, but we found reduction in mortality risk beyond 30 days. We also found risk reduction for definite stent thrombosis and any coronary revascularisation, but an increase in the risk of major bleeding from Wave-1 to Wave-2.